Produção de álcool de batata-doce variando as condições de fermentação e hidrólise (Research, Society and Development, 2020)
Bioethanol is a renewable fuel as an alternative source of energy of worldwide importance. The present study aimed to evaluate alcohol production from sweet potato, under varying reaction conditions for fermentation and hydrolysis. A genotype was selected to obtain dried flour and processed by acid hydrolysis and enzymatic hydrolysis with α-amilase and amiloglucosidase. The experiment was carried out in a completely randomized block design with three central point replicates combined with response surface methodology. The variables were pH, temperature and fermentation time. The alcohol content was determined by distillation with subsequent spectrophotometric analysis. Raw materials were characterized according to moisture, reducing sugars and starch, and 4.13%, 4.04% and 71.80% were obtained, respectively. Acid hydrolysis showed higher alcohol percentages of distilled samples. The highest values for acid hydrolysis and enzymatic hydrolysis in fermentations were 26.42% and 25.04%, respectively, carried out at pH 5.0 and 36°C for 5 days. The fermentation time was the most important variable, with higher and significant values for both types of hydrolysis. Acid hydrolysis presented higher potential for alcoholic production than enzymatic hydrolysis in sweet potato fermentation.